The Relationship Between Screen Time Duration And Speech Delay In Children Aged 0-6 Years In Malang City - Safira, Safira; Sanjaya, Ayling; Santoso, Anna Lewi (Health Notions, 2026)
Excessive screen time in early childhood can affect various aspects of development, including speech abilities. This study aims to determine the relationship between screen time duration and the occurrence of speech delay in children aged 0–6 years in Malang City. A case–control design was used with a total of 60 children, consisting of 30 children with speech delay and 30 children with normal speech development. Data were collected using a questionnaire measuring daily screen time duration and the Developmental Pre-Screening Questionnaire (KPSP) to assess developmental status. Statistical analysis using the Chi-Square test showed a significant relationship between screen time duration and speech delay (p = 0.000). The findings indicate that children exposed to screen time for more than one hour per day have a higher risk of experiencing speech delay compared to those with limited exposure. These results highlight the important role of parents in supervising and limiting the use of digital media. By reducing screen time and increasing direct interaction, children’s speech and language development can be better supported. This study concludes that managing screen time is a crucial step in preventing speech delay in early childhood